2018
DOI: 10.18805/ijar.b-992
|View full text |Cite
|
Sign up to set email alerts
|

Pathology and molecular genetics of intersexual goats: A review

Abstract: Intersex traits are serious reproductive disorders in goats, and the intersexual goat can influence development of goat husbandry. In goats, the PIS (polled intersex syndrome) mutation is responsible for both the absence of horns and sex reversal, exclusively affecting XX individuals. PIS is caused by a large deletion of goat chromosome 1q43 that affects the transcription of the genes PISRT1 and FOXL2. Here, we aim to contribute to the discussion on the pathology and molecular genetics … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…However, the amino acid sequences of RSPO1 exhibited different degrees of variation among species. Previous studies have found differences in the function of RSPO1 among different species [ 19 , 20 , 21 , 22 , 23 , 24 ]. Therefore, although RSPO1 appears to have conserved functions in ovarian development among different species, its specific mechanisms of action or associated target genes might differ.…”
Section: Discussionmentioning
confidence: 99%
“…However, the amino acid sequences of RSPO1 exhibited different degrees of variation among species. Previous studies have found differences in the function of RSPO1 among different species [ 19 , 20 , 21 , 22 , 23 , 24 ]. Therefore, although RSPO1 appears to have conserved functions in ovarian development among different species, its specific mechanisms of action or associated target genes might differ.…”
Section: Discussionmentioning
confidence: 99%